Rumen Biohydrogenation and Microbial Community Changes Upon Early Life Supplementation of 22:6n-3 Enriched Microalgae to Goats - Dewanckele, Lore; Vlaeminck, Bruno; Hernandez-Sanabria, Emma; Ruiz-González, Alexis; Debruyne, Sieglinde; Jeyanathan, Jeyamalar; Fievez, Veerle (Frontiers in Microbiology, 2018)
Dietary supplementation of docosahexaenoic acid (DHA)-enriched products inhibits the final step of biohydrogenation in the adult rumen, resulting in the accumulation of 18:1 isomers, particularly of trans(t)-11 18:1. Occasionally, a shift toward the formation of t10 intermediates at the expense of t11 intermediates can be triggered. However, whether similar impact would occur when supplementing DHA-enriched products during pregnancy or early life remains unknown. Therefore, the current in vivo study aimed to investigate the effect of a nutritional intervention with DHA in the early life of goat kids on rumen biohydrogenation and microbial community. Delivery of DHA was achieved by supplementing DHA-enriched microalgae (DHA Gold) either to the maternal diet during pregnancy (prenatal) or to the diet of the young offspring (postnatal). At the age of 12 weeks, rumen fluid was sampled for analysis of long-chain fatty acids and microbial community based on bacterial 16S rRNA amplicon sequencing. Postnatal supplementation with DHA-enriched microalgae inhibited the final biohydrogenation step, as observed in adult animals. This resulted particularly in increased ruminal proportions of t11 18:1 rather than a shift to t10 intermediates, suggesting that both young and adult goats might be less prone to dietary induced shifts toward the formation of t10 intermediates, in comparison with cows. Although Butyrivibrio species have been identified as the most important biohydrogenating bacteria, this genus was more abundant when complete biohydrogenation, i.e. 18:0 formation, was inhibited. Blautia abundance was positively correlated with 18:0 accumulation, whereas Lactobacillus spp., Dialister spp. and Bifidobacterium spp. were more abundant in situations with greater t10 accumulation. Extensive comparisons made between current results and literature data indicate that current associations between biohydrogenation intermediates and rumen bacteria in young goats align with former observations in adult ruminants.